A semi-analytical model of hydroelastic slamming. (February 2021) - Sun, Zhe; Korobkin, A.; Sui, X.P.; Zhi, Zong
Abstract: A semi-analytical model of hydroelastic slamming for two-dimensional symmetric flexible bodies is presented in this paper. The hydrodynamic loads are computed using the analytical Modified Logvinovich Model (MLM) with account for elastic deflections of the body surface. The elastic deflections are described by the modal approach. The rigid and elastic motions of the body are computed at the same time together with the wetted part of the body surface. The coupled problem of elastic impact is reduced to a system of nonlinear ordinary differential equations, which is integrated in time by the implicit Newmark method with iterations at each time step. Both free fall and constant water entry cases are considered. The developed model is validated for flexible wedge and cylindrical shell water entry problems. Good agreements with existing experimental and numerical results are achieved. It is shown that the MLM significantly improves predictions of the deflections and stresses cause by the impact compared with the Wagner model of water impact. The developed model is suitable for efficient and accurate computations of water elastic impacts.